Sticky situations: recent advances in control of cell adhesion during neuronal migration - Solecki, David J. (2012)
The migration of neurons along glial fibers from a germinal zone (GZ) to their final laminar positions is essential for morphogenesis of the developing brain, aberrations in this process are linked to profound neurodevelopmental and cognitive disorders. During this critical morphogenic movement, neurons must navigate complex migration paths, propelling their cell bodies through the dense cellular environment of the developing nervous system to their final destinations. It is not understood how neurons can successfully migrate along their glial guides through the myriad processes and cell bodies of neighboring neurons. Although much progress has been made in understanding the substrates (1–4), guidance mechanisms (5–7), cytoskeletal elements (8–10), and post-translational modifications (11–13) required for neuronal migration, we have yet to elucidate how neurons regulate their cellular interactions and adhesive specificity to follow the appropriate migratory pathways. Here I will examine recent developments in our understanding of the mechanisms controlling neuronal cell adhesion and how these mechanisms interact with crucial neurodevelopmental events, such as GZ exit, migration pathway selection, multipolar-to-radial transition, and final lamination.